COMPARATIVE ANALYSIS OF POLITENESS MAXIMS IN ENGLISH AND UZBEK LANGUAGES (TAMADDUN NURI JURNALI, 2024)
In this article, the factors of the realization of the category of politeness in English and Uzbek languages in the context of intercultural communication, the importance of a pragmatic approach in the process of communication, and the specific norms that representatives of different cultures should take into account in the process of mutual communication, and the issues of describing the category of politeness in speech etiquette are covered.